1986
DOI: 10.1088/0031-8949/33/1/007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Stark Broadening Parameters for Ar II and Xe II Lines

Abstract: Stark broadening parameters of 20 Ar II lines from the 4s-4p and 3d-4p transition arrays and of 19 Xe II lines from the 6s-6p and 5d-6p transition arrays were measured. Additional broadening mechanisms other than Stark effect were taken into account. A wall stabilized stationary cascade arc served as plasma source. Electron densities were determined with high precision from independent measurements with a two-wavelengths Michelson interferometer. The results are compared to experimental data from literature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
2
20
3
Order By: Relevance
“…Excluding these measurements, we may conclude that our theoretical Stark width calculations are in good agreement with experimental data for 6s−6p transitions. It should be noticed that our results are in excellent agreement with experimental data of Nick & Helbig (1986) and Richou et al (1984) which have the highest accuracy among critically selected experimental data for Xe II lines in Konjević & Wiese (1990). Our theoretical results are in excellent agreement as well with the experimental values of Vitel & Skowronek (1987) and Konjević & Uzelac (1990).…”
Section: Results and Discusionsupporting
confidence: 87%
See 2 more Smart Citations
“…Excluding these measurements, we may conclude that our theoretical Stark width calculations are in good agreement with experimental data for 6s−6p transitions. It should be noticed that our results are in excellent agreement with experimental data of Nick & Helbig (1986) and Richou et al (1984) which have the highest accuracy among critically selected experimental data for Xe II lines in Konjević & Wiese (1990). Our theoretical results are in excellent agreement as well with the experimental values of Vitel & Skowronek (1987) and Konjević & Uzelac (1990).…”
Section: Results and Discusionsupporting
confidence: 87%
“…The values obtained for temperatures from 5000 K up to 50000 K and an electron density of 10 23 m −3 are compared (in Table 2 and in Figs. 1-4) with the available experimental data Miller et al 1981;Richou et al 1984;Nick & Helbig 1986;Vitel & Skowronek 1987;Manola et al 1988;Lesage et al 1989;Di Rocco 1990b;Konjević & Uzelac 1990;Bertuccelli et al 1991;Gigosos et al 1994). Since we found that the ion broadening contribution is about several per cent, only the electron broadening contribution is given.…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) vary for about ±50% around the average value. Exceptions are the results in Jalufka et al (1966) and Abbas et al (1988), which are too high and some results in Vaessen et al (1985) and Nick & Helbig (1986), which are slightly lower than the other results. The Ar II halfwidth results corresponding to 4p−4d transitions (Fig.…”
Section: Analysis Of the Stark Halfwidthscontrasting
confidence: 67%
“…(1) For evaluation of the Stark component of our ArII lines we have applied the half-widths obtained by Helbig and Nick [27] and the electron density values listed in column 3 of Table I (based on Griem's broadening parameters). By comparing the directly measured line profile with the convolution of the evaluated Stark profile, the instrumental profile (Airy function), and a Gauss profile, the last contribution (the Doppler width) was determined.…”
Section: Table Imentioning
confidence: 99%